2022
DOI: 10.1177/21582440221102421
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Non-Performing Loans in the Indonesian Banking Industry: An Asymmetric Approach Before and During the Pandemic Crisis

Abstract: The outbreak has created an unprecedented crisis that influences macroeconomic variables. These circumstances are predicted to be contagious for banking performance. To understand the related influences, this study attempts to examine the asymmetric relationship between macroeconomic variables and non-performing loans/financing of the Indonesian banking industry before and during the COVID-19 pandemic. The nonlinear autoregressive distributed lag (NARDL) is adopted based on the time-series data from 2005Q1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
4
11
0
Order By: Relevance
“…Anita et al ( 2022 ) documented that government budget balance positively impacts banks’ NPLs in South Asian Association for Regional Cooperation (SAARC) economies while GDP, sovereign debt, inflation rate, and money supply have a negative impact on banks’ NPLs. Similarly, Fakhrunnas et al ( 2022 ) revealed an asymmetric nexus between macroeconomic factors and the banks’ NPLs in Indonesia both before and during the COVID-19 pandemic. Foglia ( 2022 ) underlined that GDP and public debt negatively impact NPLs in the Italian banking system whereas the unemployment rate and domestic credit have the opposite effect.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Anita et al ( 2022 ) documented that government budget balance positively impacts banks’ NPLs in South Asian Association for Regional Cooperation (SAARC) economies while GDP, sovereign debt, inflation rate, and money supply have a negative impact on banks’ NPLs. Similarly, Fakhrunnas et al ( 2022 ) revealed an asymmetric nexus between macroeconomic factors and the banks’ NPLs in Indonesia both before and during the COVID-19 pandemic. Foglia ( 2022 ) underlined that GDP and public debt negatively impact NPLs in the Italian banking system whereas the unemployment rate and domestic credit have the opposite effect.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Secondly, the study provides a new viewpoint by examining Islamic banking performance focusing on profitability and financial stability. We acknowledge that Etikonomi Volume 23 (1), 2024: 201 -218 the previous studies already explained how the COVID-19 pandemic affects banking performance, such as Fakhrunnas et al (2022) concerning the asymmetric effect of risk performance, Anto et al (2022) and Fakhrunnas et al (2021) examining the performance of the credit risk in Islamic bank'sbank's home financing, Elnahass et al (2021) measured the global banking performance using risk and return perspective, but they did not provide sufficient observation of Islamic bank while Li et al (2021) concern on how the outbreak affect income diversification of in banking industry. The studies mentioned above need to be extended to examine the impact of COVID-19 on Islamic banking performance more comprehensively.…”
Section: Introductionmentioning
confidence: 95%
“…Other relevant previous studies examine the asymmetric effect of the COVID-19 pandemic on Islamic banking stability in Indonesia, which Fakhrunnas et al (2022) studied. The findings explain that macroeconomic variables' impact on Islamic banks' nonperforming financing during the pandemic was asymmetrical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Nepal's present legislative framework and institutional structure are unfavorable to the growth of the entire economic and private sectors, there is an urgent need for reformation in both areas. According to Fakhrunnas et al (2022), the pandemic has substantially influenced the real economy, notably in the tourism and transportation sectors. According to Erdas and Ezanoglu (2022), the banking industry is critical to the health of the economy and its prosperity.…”
Section: Introductionmentioning
confidence: 99%